Screening of some fungal isolates for lipase production and optimization of cultural conditions for the most potent isolate - Osman, M. E.; Abo El-Nasr, Amany A.; Abdullah, Nashwa H. (2012)
Sixteen Fungal isolates were screened for lipase production. Trichoderma viride was the most promising isolate for lipase activity. Lipase production has been optimized by this isolate using the following conditions; pH 6.0, temperature 25°C and 6 days of incubation. Moreover, the enzyme production has been enhanced by supplementing the production medium with egg yolk as only carbon source. Starch also resulted in an increase in lipase production. The production of the lipase enzyme in medium devoid from the lipid sources proves that, this lipase is partially a constitutive enzyme. Fungal discs have been found to be the most suitable inoculum. Aeration has been proved to be favored for lipase production. The static condition was advantages than the agitation for the lipase activity. Peptone as organic N-source, sodium nitrate as inorganic N- source and KH2Po4 as phosphate source were more suitable for lipase production. One tenth percent oil concentration (w/v) was the best for lipase production. Keywords: Lipase, Trichoderma viride.
Includes references.
Summary in Arabic.
1
Keywords: Lipase; Trichoderma viride; Fungi -- isolation & purification